Memperkuat OCB: Peran penting Pemberdayaan Psikologis pada Pegawai UKM Dibidang Makanan (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2022)
Promoting SMEs is the right step to develop the community's economy, and empowerment is the right way. This study aims to examine the role of psychological empowerment as a mediator on the influence of transformational leaders in forming Organizational Citizenship Behavior (OCB) of their subordinates. The study used 4 SMEs in Kabupaten Bantul and Sleman as population and used saturated sampling technique. Data were collected from employees using a closed questionnaire instrument. The research findings have managerial implications that SMEs need to strengthen employee OCB through psychological empowerment.